A Study on the Value of promotion in the telecom industry of India - Agarwal, Varsha (IJARIIT, 2022)
(Gaj, 2022) Promotion is a type of marketing communication that is used in many sectors and in a variety of situations to help businesses achieve their goals, including bringing in new customers and retaining existing ones while also fostering customer loyalty. This research study offers a thorough examination of how promotion plays a role in influencing customers in India's evolving telecom market. This study delves further into the various promotional strategies employed by businesses like Airtel, BSNL, Vodafone Idea (VI), and Jio to attract customers and urge them to utilize their telecom services. The research looked at Jio's marketing approach of offering free internet and telecom service for three months after its start, and how this enabled Jio draw in a lot of customers and grow into a significant business following its arrival. The research study also concentrated on the relationship between successful promotion and the development of consumer loyalty and a positive brand image for the business. Therefore, the study looks after the importance of promotion in the telecom industry can lead to a significant change in the buying behavior of the consumers in India and also how it has helped the companies to gain a better position in the market by improving their market share.
ISME
Keywords: Promotion; Consumer Loyalty; Brand Loyalty; Marketing Communication